2017
DOI: 10.17533/udea.rccp.v30n4a02
|View full text |Cite
|
Sign up to set email alerts
|

Rumen fermentation and digestibility of spent mushroom (Pleurotus ostreatus) substrate inoculated with Lactobacillus brevis for Hanwoo steers

Abstract: Original articles 267Rumen fermentation and digestibility of spent mushroom (Pleurotus ostreatus) substrate inoculated with Lactobacillus brevis for Hanwoo steers ¤ Fermentación ruminal y digestibilidad de la cama de champiñón (Pleurotus ostreatus) desechada inoculada con Lactobacillus brevis en novillos Hanwoo Fermentação ruminal e digestibilidade de resíduo de substrato de cogumelo (Pleurotus ostreatus) inoculado com Lactobacillus brevis en novilhos Hanwoo AbstractBackground: Ensiling spent mushroom substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 18 publications
3
11
1
Order By: Relevance
“…Some studies have reported the effectiveness of LAB inoculation on in vitro ruminal fermentation characteristics [1,35,36]. Lack of effect on rumen pH and NH 3 -N after 15 and 30 days of ensiling among the LAB treatments in this study was contrary to the results of [8].…”
Section: In Vitro Rumen Fermentation Characteristics Methane Production and Dm Digestibilitycontrasting
confidence: 97%
“…Some studies have reported the effectiveness of LAB inoculation on in vitro ruminal fermentation characteristics [1,35,36]. Lack of effect on rumen pH and NH 3 -N after 15 and 30 days of ensiling among the LAB treatments in this study was contrary to the results of [8].…”
Section: In Vitro Rumen Fermentation Characteristics Methane Production and Dm Digestibilitycontrasting
confidence: 97%
“…As expected, the TMRs inoculated with L. acidophilus and B. subtilis had a higher LAB count, whereas molds were inhibited due to the antifungal properties of the inoculant [28,29]. Several studies showed that bacterial inoculation of silage could cause a decrease in pH during fermentation [30]. Lower pH in silage indicates good fermentation and quality of ensiled forage [31].…”
Section: Discussionmentioning
confidence: 77%
“…Inoculation of SMS with Lactobacillus , Bacillus , or Enterobacte r spp. ensures rapid acidification, and increases dry matter degradability and crude protein content [ 64 , 66 , 70 , 75 , 77 , 78 ].…”
Section: Spent Mushroom Substrate As Feedmentioning
confidence: 99%